2017
DOI: 10.1002/elan.201700045
|View full text |Cite
|
Sign up to set email alerts
|

Flow Injection Amperometric Analysis of H2O2 at Platinum Nanoparticles Modified Pencil Graphite Electrode

Abstract: A Pt nanoparticle modified Pencil Graphite Electrode (PGE) was proposed for the electrocatalytic oxidation and non‐enzymatic determination of H2O2 in Flow Injection Analysis (FIA) system. Platinum nanoparticles (PtNPs) electrochemically deposited on pretreated PGE (p.PGE) surface by recording cyclic voltammograms of 1.0 mM of H2PtCl6 solution in 0.10 M KCl at scan rate of 50 mV s−1 for 30 cycles. Cyclic voltammograms show that the oxidation peak potential of H2O2 shifts from about +700 mV at bare PGE to +50 mV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…7A). Ascorbic acid was studied separately since it is usually the most problematic interfering compound in the determination of H2O2 [45,46]. Fig.…”
Section: Effect Of Interferencesmentioning
confidence: 99%
“…7A). Ascorbic acid was studied separately since it is usually the most problematic interfering compound in the determination of H2O2 [45,46]. Fig.…”
Section: Effect Of Interferencesmentioning
confidence: 99%
“…The good recovery percentage (95.2–96.2 %) and interference study demonstrated the selectivity toward the complex sample matrices. Pt nanoparticle modified pencil graphite electrode was applied in the first flow injection amperometric analysis of H 2 O 2 , which was successfully applied to determination of H 2 O 2 in a hair dye sample . Due to the wide presence, it is quite reasonable for environmental H 2 O 2 detection …”
Section: Application Of Free‐standing 3d Electrodesmentioning
confidence: 99%
“…was applied in the first flow injection amperometric analysis of H 2 O 2 , which was successfully applied to determination of H 2 O 2 in a hair dye sample. [163] Due to the wide presence, it is quite reasonable for environmental H 2 O 2 detection. [164]…”
Section: Electrochemical Detection Of H 2 O 2 For Everyday Samplesmentioning
confidence: 99%
“…In H 2 O 2 assay, the modified electrodes prepared by covering bare electrode surfaces with metallic/bimetallic nanoparticles, carbon nanotubes, metal oxides, graphene or their hybrids are the most extensively used electrodes. [19][20][21][22][23][24][25][26] Moreover, one of the most efficient ways is the preparation of modified electrodes with redox active mediators which increase the rate of electron transfer between analyte and electrode. Thus CMEs prepared with different types of mediators have been reported for the determination of H 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, PGE has been extensively used in the development of electrochemical sensors/biosensors due to its favorable functions such as disposability, cheapness, commercial availability, ease of modification, etc. [21,22,26,[53][54][55][56] Thus, the novelty of this study is the introduction of a disposable, fast, sensitive, cheap amperometric H 2 O 2 sensor in FIA system as well as the use of the CUPRAC reagent (i. e. [Cu(Nc) 2 ] 2 + complex) as a new redox mediator for electrode modification in the electrocatalytic oxidation of H 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%